2021
DOI: 10.1128/jvi.00714-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Defective Viral Genomes in Ebola Virus-Infected Rhesus Macaques

Abstract: Ebola virus (EBOV), of the family Filoviridae, is an RNA virus that can cause hemorrhagic fever with a high mortality rate. Defective viral genomes (DVGs) are truncated genomes that have been observed during multiple RNA virus infections, including  in vitro EBOV infection, and have previously been associated with viral persistence and immunostimulatory activity. As DVGs have been detected in cells persistently infected with EBOV, we hypothesized that DVGs may al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The approach of sequence analysis used in this study is an effective means of determining the consensus sequence but is not as accurate in describing the RNA molecules late in infection. Analysis of the RNA genomes during the course of Ebola infection has shown that defective truncated panhandle genomes accumulate late in infection [33]. In another SUDV natural history study performed at another BSL-4 facility, viral RNA was enriched by selecting out ribosomal and messenger RNA and analyzing the resulting cDNA library for evidence of defective genomes [34].…”
Section: Discussionmentioning
confidence: 99%
“…The approach of sequence analysis used in this study is an effective means of determining the consensus sequence but is not as accurate in describing the RNA molecules late in infection. Analysis of the RNA genomes during the course of Ebola infection has shown that defective truncated panhandle genomes accumulate late in infection [33]. In another SUDV natural history study performed at another BSL-4 facility, viral RNA was enriched by selecting out ribosomal and messenger RNA and analyzing the resulting cDNA library for evidence of defective genomes [34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in lung infection with RSV, early production of DVGs activates RIG-I-like receptors to stimulate the activation of IRF3 and IRF1, leading to production of TNFα, IFNλ, and IFIT1, suppression of virus replication, and survival of persistently infected cells [ 136 , 139 , 140 ]. DVGs have been demonstrated in the testes during filovirus infection of nonhuman primates [ 141 ] and in the lungs of children with RSV infection [ 140 ].…”
Section: How Do Rna Viruses Evade the Immune System To Persist?mentioning
confidence: 99%
“…Regarding laboratory experiments, there is still no published in vivo study demonstrating sexual transmission. However, several studies in macaques and guinea pigs have found virus genome or antigen in tissues, and glands of the male but also female genital system following an intra-muscular or peritoneal challenge ( Cooper et al, 2018 ; Liu et al, 2022 ; Perry et al, 2018 ; Baskerville et al, 1985 ; Johnson et al, 2021 ; Zeng et al, 2017 ). This suggests that both genders can be infectious and ultimately infect their partners by the sexual route.…”
Section: Introductionmentioning
confidence: 99%